When children shape their families: Evocative effects analysis of 40,000 trios from the Norwegian Mother, Father and Child Cohort Study - Evelina T. Akimova; Agnes Fauske; Ruth Eva Jørgensen; Alexandra Havdahl; Elizabeth C. Corfield; Melinda C. Mills; Torkild Hovde Lyngstad (Proceedings of the National Academy of Sciences, 2026)
Family demographic behavior is often studied as a response to structural conditions or parental characteristics, yet children may themselves shape key family trajectories through evocative gene–environment correlations. This study is based on the Norwegian Mother, Father and Child Cohort Study (MoBa). By analyzing ~ 40,000 genotyped mother–father–child trios, we test whether children’s polygenic indices (PGIs) predict parents’ subsequent fertility, partnership dissolution, and transition to marriage. Accounting for parental PGIs, we found limited evidence for evocative effects across most traits. The exception was that higher child ADHD PGI predicted increased parental partnership dissolution (7% [CI = 2.9 to 11.8%] per SD), especially in families with daughters (11% [CI = 4.9 to 18%] per SD), higher socioeconomic status (15% [CI = 7.7 to 23.2%] per SD), and older maternal age at first birth (10% [CI = 3 to 17%] per SD). The main source of variation is the socioeconomic dimension where child-driven effects are stronger in higher-SES families. The study provides evidence for evocative gene–environment correlations in family demography, demonstrating the importance of child-to-parent effects in shaping family trajectories.